Frontier Missionary Life - Thrift, Charles T. (Church history, 1937)
Most of the people to whom the missionaries of the American Home Missionary Society ministered in the South were leading the rugged lives of frontiersmen, and frontier life is never easy. The missionaries themselves, though usually far above the average frontiersman in educational achievements, were not exempt from the hardships and privations of the frontier. Indeed the very nature of their tasks often made them feel the harshness of their environment even more keenly than did the average settler. In the maze of theological problems, interdenominational conflicts, slavery agitation, and the routine duties of a missionary, one easily loses sight of the fact that the principals involved in all these enterprises were self-sacrificing men of high ambition. Frequently they were men with families, from the more thickly settled North. The purpose of this essay is to call attention to the human side of the missionary enterprise, the suffering entailed by the lack of material possessions, by the lack of books, by sickness, and sometimes by physical violence at the hands of fellow-men. The hardships to which the missionaries were subjected changed progressively with the shifting Southern frontiers.